Bridging Prosperity: Unravelling the Interplay of Public Borrowing, Gross Capital Formation, and Economic Growth In The Nepalese Economy - Dahal Arjun Kumar; Bhattarai Ganesh; Budhathoki Prem Bahadur; Adhikari Gyan Mani (Financial Internet Quarterly)
This study investigates the impact of public borrowing and total capital formation on Nepal’s economic growth. The analysis relies on secondary data from publications from the Nepal Rastra Bank and economic surveys conducted in Nepal. The dataset has 34 consecutive yearly data points from 1988/89 to 2021/22. A causal correlational research design is used. It is guided by positivist research philosophy and deductive reasoning. The robust least square method is employed to explore the impact of independent variables. Research indicates that public debt and capital formation favourably and significantly affect Nepal’s economic growth. The study demonstrates that a one-unit rise in public debt and capital formation leads to 0.2881 and 0.6205 unit increases in Nepal’s economic growth, respectively. The positive impact of capital formation is more effective than public borrowing in promoting the economic growth of Nepal. Policymakers should focus on creating a business-friendly environment, enacting growth-oriented fiscal and monetary policies, efficiently allocating resources for infrastructure and technology, and managing public debt prudently to ensure sustainable and equitable economic development.